Problems of Students' Verbal Speaking Ability in Indonesian Language Learning - Sopi Ali Mubarok; Aditya Ansor Alsunah; Deasy Aditya Damayanti; Ardi Mulyana Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Speaking ability is a crucial language skill in learning Indonesian because it plays an important role in the development of students' thinking, communication, and confidence skills. However, the reality of learning shows that students' verbal speaking skills are still relatively low. This study aims to identify the challenges of verbal speaking skills of students of SMP Satu Atap 4 Culamega in learning Indonesian, the factors that cause them, and alternative learning solutions that can be applied. This study uses a descriptive qualitative approach. Data collection techniques include learning observations, interviews with teachers and students, and documentation studies on Indonesian teaching materials. Data is analyzed through the stages of data reduction, data presentation, and thematic conclusion drawn. The results of the study showed that students experienced difficulties in mastering active vocabulary, fluency in speaking, and the ability to express ideas orally in the form of monologues and academic dialogues. The findings of the study revealed that low verbal speaking skills are influenced by the limitations of the family language environment, learning methods that are still theory-oriented, and the strong influence of mother tongue. This research provides theoretical benefits for the development of Indonesian language learning studies and practical benefits for teachers in designing more communicative and contextual speaking learning.